New directions and paradigms for the study of Greek architecture : interdisciplinary dialogues in the field - Sapirstein, Philip,; Scahill, David, (Monumenta Graeca et Romana;, 2020)
"New Directions and Paradigms for the Study of Greek Architecture comprises 20 chapters by nearly three dozen scholars who describe recent discoveries, new theoretical frameworks, and applications of cutting-edge techniques in their architectural research. The contributions are united by several broad themes that represent the current directions of study in the field, i.e.: the organization and techniques used by ancient Greek builders and designers; the use and life history of Greek monuments over time; the communication of ancient monuments with their intended audiences together with their reception by later viewers; the mining of large sets of architectural data for socio-economic inference; and the recreation and simulation of audio-visual experiences of ancient monuments and sites by means of digital technologies. Contributors are: Lena Lambrinou; Vasileia Manidaki; Jeanne Capelle; Alexander Tanner; Nancy L. Klein; Nils Hellner; D. Matthew Buell, John C. McEnroe, Jorge Andreas Botero Besadalombana, Rafał Bieńkowski; Yannos Kourayos, Kornilia Daifa, Goulielmos Orestidis, Dimitrios Egglezos, Vasilis Papavasileiou, Eleni-Eva Toumpakari; Kyle A. Jazwa; András Patay-Horváth; Mark Wilson Jones; Silke Müth; Sarah A. Rous; Matthias Grawehr; Mary B. Hollinshead; Miriam G. Clinton, Ansel MacLaughlin; Christian Fron, Verena Stappmanns, Xiaoru Zhou, Philip Leistner; Clemente Marconi, David Scahill, Massimo Limoncelli; Bonna D. Wescoat".